The role of animals in emerging viral diseases - Johnson, Nicholas, 1968- (Academic Press, 2014)
Presents what is currently known about the role of animals in the emergence or re-emergence of viruses including HIV-AIDS, SARS, Ebola, avian flu, swine flu, and rabies. It presents the structure, genome, and methods of transmission that influence emergence and considers non-viral factors that favor emergence, such as animal domestication, human demography, population growth, human behavior, and land-use changes.